Financial Organization and Operations of the IMF. (Pamphlet Series; Pamphlet Series, 1998)
The financial structure and operations of the IMF are described in this pamphlet, as well as the sources of IMF financing, the policies associated with the use of IMF resources, and the role of the IMF as trustee to various accounts that are administered by it.